The Age of Marriage on Interdisiplinary Islamic Law Perspectives - Iwan Romadhan Sitorus; Yusmita Yusmita (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2020)
The Act No. 16 of 2019 is an amendment to The Act No. 1 of 1974. The article 7 provides the age limit for each person who will marry at the age of 19 years for both men and women. The age limit given by the law does not look comprehensively in biological, sociological readiness, and so forth. The modified law should be able to produce the benefit of the husband and wife in fostering the household. This is because determining the age of marriage aims to maintain lineage, quality of offspring, patterns of family relationships, diversity in the family, and to prepare for maturity in the economy by taking into account various aspects such as psychological, sociological, and biological aspects. In this regard, the authors offer to reconstruct the provisions to 19 years for women and 21 years for men. This is based on consideration of the biological, psychological, and socio-cultural aspects of Indonesian society. By the age of 21, men are considered to reach maturity in their attitude, able to act, and responsible for their actions. Whereas a 19-year-old woman is considered to be an adult and able to run a household life.